Pelatihan Penyusunan Lembar Kerja Siswa (LKS) Bagi Guru Matematika SMP di Telukjambe, Karawang - Kiki Nia Sania Effendi; Indrie Noor Aini (Universitas Mathla'ul Anwar Banten, 2018)
WORKSHOP OF STUDENT WORKSHEET COMPILATION FOR MATHEMATICS TEACHERS OF JUNIOR HIGH SCHOOL IN TELUKJAMBE, KARAWANG. The majority of math teachers use Student Worksheet (LKS) traded by the publisher’s distributor. The contents of LKS are less interesting and innovative. LKS does not help the participants to collect the material and learn their interest in mathematics learning. None or steps in the LKS which allows participants to discuss the concepts they are studying. According to the theory of constructivism a learner in learning must be able to mengkontruksi knowledge to understand a material. On that basis, we prepare training on the preparation of LKS. Activities undertaken through socialization with methods that in this devotion program is a method of lectures and exercises supported by discussion and question and answer. Output target after the implementation of this Program is the increase of the ability of Junior High School teachers who teach in class VII in preparing the LKS as well as the product of LKS.